2015
DOI: 10.1007/s00429-015-1075-y
|View full text |Cite
|
Sign up to set email alerts
|

Impaired and preserved aspects of feedback learning in aMCI: contributions of structural connectivity

Abstract: Distinct lines of research demonstrated that patients with amnestic mild cognitive impairment (aMCI), a potential precursor of Alzheimer disease (AD), are particularly impaired in remembering relations between items and that the use of emotional targets can facilitate memory in patients with AD. We link these findings by examining learning through positive and negative feedback in patients with aMCI, and explore its anatomic underpinnings with diffusion tensor imaging and tractography. Compared to healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 83 publications
1
11
0
Order By: Relevance
“…In general, the asymmetrical cerebral involvement in AD is considered to be nondirectional, or as Derflinger and colleagues describe it, "asymmetric but not lateralized" [4,5]. However, a number of studies have reported consistent left-lateralized damage in AD, particularly to the hippocampus and white matter integrity [10][11][12][13][14], and also in terms of amyloid and tau pathology [6,15]. Furthermore, the degree of leftward cerebral asymmetry has been associated with disease progression and progressively declining cognitive performance [6,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the asymmetrical cerebral involvement in AD is considered to be nondirectional, or as Derflinger and colleagues describe it, "asymmetric but not lateralized" [4,5]. However, a number of studies have reported consistent left-lateralized damage in AD, particularly to the hippocampus and white matter integrity [10][11][12][13][14], and also in terms of amyloid and tau pathology [6,15]. Furthermore, the degree of leftward cerebral asymmetry has been associated with disease progression and progressively declining cognitive performance [6,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Atrophy in AD is asymmetrical across a wide range of brain structures, such as the medial temporal lobe [16], hippocampus [2,5,12,17], amygdala [5], and caudate [5]. Asymmetries have also been found in terms of white matter integrity, neural connectivity [11,13], cerebral metabolism [6,18], amyloid‐β deposition [6], and tau pathology [15]. Amyloid and tau asymmetries are positively correlated across regions typically affected with AD pathology, suggesting that the two pathologies interact locally [19].…”
Section: Introductionmentioning
confidence: 99%
“…The same pathological asymmetries were found in the Mild Cognitive Impairment (MCI). Indeed, a large number of morphological-based studies have previously reported a variety of regional abnormalities in hemispheric asymmetry in AD and MCI, including cortical thickness (Kim et al, 2012 ), cortical volumes (Müller et al, 2005 ; Pennanen et al, 2005 ; Shi et al, 2009 ; Cherbuin et al, 2010 ; Derflinger et al, 2011 ; Dhikav et al, 2016 ; Li et al, 2016 ), cortical surface area (Thompson et al, 2003 , 2007 ; Long et al, 2013 ), as well as white matter properties (Müller et al, 2005 ; Damoiseaux et al, 2009 ; Stricker et al, 2009 ; Liu et al, 2011 ; Wessa et al, 2016 ; Yang et al, 2017 ) and functional connectivity (Wang et al, 2015 , 2016 ). The majority of these studies showed that the left hemisphere had a smaller volume than the right, indicating a faster left hemisphere atrophy than in the right side in AD (Thompson et al, 2003 , 2007 ; Müller et al, 2005 ; Damoiseaux et al, 2009 ; Li et al, 2016 ; Wessa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous neuroimaging studies have demonstrated aberrant hemispheric asymmetry of both brain structure and function in AD and MCI, including cortical thickness ( Kim et al, 2012 ), cortical volume ( Müller et al, 2005 ; Pennanen et al, 2005 ; Shi et al, 2009 ; Cherbuin et al, 2010 ; Derflinger et al, 2011 ; Dhikav et al, 2016 ; Li et al, 2016 ), and cortical surface area covarying across the brain ( Thompson et al, 2003 , 2007 ; Long et al, 2013 ). There is also aberrant hemispheric asymmetry in WM properties ( Müller et al, 2005 ; Damoiseaux et al, 2009 ; Stricker et al, 2009 ; Liu et al, 2011 ; Wessa et al, 2016 ) and functional connectivity ( Wang et al, 2006 , 2015 ). Intriguingly, some of these studies showed that the left hemisphere was significantly more impaired than the right, indicating a faster left hemisphere degeneration in AD ( Thompson et al, 2003 , 2007 ; Müller et al, 2005 ; Damoiseaux et al, 2009 ; Li et al, 2016 ; Wessa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also aberrant hemispheric asymmetry in WM properties ( Müller et al, 2005 ; Damoiseaux et al, 2009 ; Stricker et al, 2009 ; Liu et al, 2011 ; Wessa et al, 2016 ) and functional connectivity ( Wang et al, 2006 , 2015 ). Intriguingly, some of these studies showed that the left hemisphere was significantly more impaired than the right, indicating a faster left hemisphere degeneration in AD ( Thompson et al, 2003 , 2007 ; Müller et al, 2005 ; Damoiseaux et al, 2009 ; Li et al, 2016 ; Wessa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%